Redesigning Off - Grid Solar Home System Pricing in Munger District of Bihar : A Case Study - Irshad Ali, Md.; Yadav, Manmohan (Prabandhan: Indian Journal of Management, 2018)
This case study discussed the challenges faced in designing solar home systems and providing solar energy options to rural households in Munger District of Bihar by two social enterprises - SEWA Bharat and SELCO. The findings of the primary research revealed that deep understanding of consumer needs and affordability can help develop innovative & customized solutions to the energy - deficit in rural India. Such innovations not only promote renewable energy product acceptance at the consumer level, but also help the country reduce its energy intensity. The primary data were collected by us through personal interviews of SEWA Bharat employees and individual households during January-March 2016.